Gibberellin-regulated proteins: Emergent allergens - Iizuka, T.; Barre, A.; Rougé, P.; Charpin, D.; Scala, E.; Baudin, B.; Aizawa, T.; Sénéchal, H.; Poncet, P. (Frontiers in Allergy, 2022)
About ten years ago a protein family was shown for the first time to contain allergenic members, gibberellin-regulated protein (GRP). The first reported member was from peach, Pru p 7. One can hypothesized that it was not detected before because its physico-chemical characteristics overlap with those of LTP, a well known allergen and/or because GRP expression level, in contrast to now, was under a sensitizing threshold. Like LTPs, GRPs are small cationic proteins with disulfide bridges, are resistant to heat and proteolytic cleavage and are involved in the defense of the plant. Besides peach, GRP allergens have been described in Japanese apricot sweet cherry, orange, pomegranate, bell pepper and also in pollen with a restriction to Cupressaceae tree family. IgE cross-reactivities were described between GRPs and the reported peach/cypress and citrus/cypress syndromes may therefore be explained because of these GRP cross-reactivities. GRPs are clinically relevant and severe adverse reactions may sometimes occur in association with cofactors. More than 60% and up to 95% sequence identities are calculated between the various allergenic GRPs and 3-dimensional models show a cleft in the molecule and allows the prediction of, at least, 3 epitopic regions. The structure of the protein as well as its properties and the matrix effect in the original allergenic source should be unravelled to understand why, despite the ubiquity of the protein family in plants, only a few members are able to sensitize patients.